Can PjBL Improve Vocational High School Students' Learning Outcomes? Effectiveness Test of Accounting Subjects - Sri Liawati; Nina Oktarina; Rusdarti (Journal of Economic Education, 2025)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) learning model in improving accounting learning outcomes for Vocational High School (SMK) students. This study was conducted using a qualitative descriptive method based on literature study. Data were obtained through a comprehensive analysis of various relevant scientific articles regarding the application of PjBL in accounting learning in SMK. The literature review shows that PjBL consistently provides a significant positive effect on improving student learning outcomes, both in cognitive and psychomotor aspects. This model encourages active student participation through contextual, collaborative, and problem-solving-based project work. Various studies have reported an increase in student average grades and classical learning completion rates after the implementation of PjBL. In addition, important skills such as critical thinking, communication, and teamwork skills also increase. The implementation of PjBL is an effective innovative learning strategy to improve the quality of vocational education, especially in the field of accounting, because it is able to improve learning outcomes and develop various student skills.